At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To rewrite the equation [tex]\(4x^2 - 9y^2 + 24x + 18y - 9 = 0\)[/tex] in standard form and identify the key features of the graph, follow these steps:
### Step 1: Group and Complete the Square
Group the x and y terms:
[tex]\[ 4x^2 + 24x - 9y^2 + 18y - 9 = 0 \][/tex]
#### For [tex]\(x\)[/tex]-Terms
Isolate and factor out the coefficient of [tex]\(x^2\)[/tex]:
[tex]\[ 4(x^2 + 6x) \][/tex]
To complete the square for [tex]\( x^2 + 6x \)[/tex]:
1. Take half the coefficient of [tex]\( x \)[/tex]: [tex]\( \frac{6}{2} = 3 \)[/tex]
2. Square it: [tex]\( 3^2 = 9 \)[/tex]
So, we rewrite [tex]\( x^2 + 6x \)[/tex] as:
[tex]\[ x^2 + 6x + 9 - 9 \][/tex]
Now we factor and adjust:
[tex]\[ 4(x^2 + 6x + 9 - 9) = 4((x + 3)^2 - 9) = 4(x + 3)^2 - 36 \][/tex]
#### For [tex]\(y\)[/tex]-Terms
Isolate and factor out the coefficient of [tex]\( y^2 \)[/tex]:
[tex]\[ -9(y^2 - 2y) \][/tex]
To complete the square for [tex]\( y^2 - 2y \)[/tex]:
1. Take half the coefficient of [tex]\( y \)[/tex]: [tex]\( \frac{-2}{2} = -1 \)[/tex]
2. Square it: [tex]\((-1)^2 = 1 \)[/tex]
So, we rewrite [tex]\( y^2 - 2y \)[/tex] as:
[tex]\[ y^2 - 2y + 1 - 1 \][/tex]
Now we factor and adjust:
[tex]\[ -9(y^2 - 2y + 1 - 1) = -9((y - 1)^2 - 1) = -9(y - 1)^2 + 9 \][/tex]
### Step 2: Combine All Parts
Combine the completed squares:
[tex]\[ 4(x + 3)^2 - 36 - 9(y - 1)^2 + 9 - 9 = 0 \][/tex]
Simplify:
[tex]\[ 4(x + 3)^2 - 9(y - 1)^2 - 36 + 9 - 9 = 0 \][/tex]
[tex]\[ 4(x + 3)^2 - 9(y - 1)^2 - 36 = 0 \][/tex]
Move the constant to the other side and simplify:
[tex]\[ 4(x + 3)^2 - 9(y - 1)^2 = 36 \][/tex]
Divide both sides by 36:
[tex]\[ \frac{4(x + 3)^2}{36} - \frac{9(y - 1)^2}{36} = \frac{36}{36} \][/tex]
[tex]\[ \frac{(x + 3)^2}{9} - \frac{(y - 1)^2}{4} = 1 \][/tex]
Here, the equation is now in standard form.
### Step 3: Identify Key Features
Center (h, k):
In the standard form [tex]\(\frac{(x - h)^2}{a^2} - \frac{(y - k)^2}{b^2} = 1\)[/tex], we have:
[tex]\[ \frac{(x - (-3))^2}{9} - \frac{(y - 1)^2}{4} = 1 \][/tex]
So, the center is:
[tex]\[h = -3, \quad k = 1\][/tex]
Values of [tex]\(a^2\)[/tex] and [tex]\(b^2\)[/tex]:
[tex]\[a^2 = 9, \quad b^2 = 4\][/tex]
Slope of the Asymptotes:
The slopes of the asymptotes of the hyperbola given by [tex]\(\frac{(x - h)^2}{a^2} - \frac{(y - k)^2}{b^2} = 1\)[/tex] are given by [tex]\(\pm \frac{b}{a}\)[/tex]:
[tex]\[ \text{slope of asymptotes} = \pm \frac{b}{a} = \pm \frac{\sqrt{4}}{\sqrt{9}} = \pm \frac{2}{3} \][/tex]
### Summary of Key Features:
- Center:
[tex]\[h = -3\][/tex]
[tex]\[k = 1\][/tex]
- Values:
[tex]\[a^2 = 9\][/tex]
[tex]\[b^2 = 4\][/tex]
- Slope of the asymptotes:
[tex]\[ \text{slope} = \pm \frac{2}{3} \][/tex]
### Answer:
In conclusion, the key features are:
[tex]\[ h = -3, \quad k = 1, \][/tex]
[tex]\[ a^2 = 9, \quad b = \sqrt{4} = 2,\][/tex]
[tex]\[ \text{slope of asymptotes} = \pm \frac{2}{3} \][/tex]
### Step 1: Group and Complete the Square
Group the x and y terms:
[tex]\[ 4x^2 + 24x - 9y^2 + 18y - 9 = 0 \][/tex]
#### For [tex]\(x\)[/tex]-Terms
Isolate and factor out the coefficient of [tex]\(x^2\)[/tex]:
[tex]\[ 4(x^2 + 6x) \][/tex]
To complete the square for [tex]\( x^2 + 6x \)[/tex]:
1. Take half the coefficient of [tex]\( x \)[/tex]: [tex]\( \frac{6}{2} = 3 \)[/tex]
2. Square it: [tex]\( 3^2 = 9 \)[/tex]
So, we rewrite [tex]\( x^2 + 6x \)[/tex] as:
[tex]\[ x^2 + 6x + 9 - 9 \][/tex]
Now we factor and adjust:
[tex]\[ 4(x^2 + 6x + 9 - 9) = 4((x + 3)^2 - 9) = 4(x + 3)^2 - 36 \][/tex]
#### For [tex]\(y\)[/tex]-Terms
Isolate and factor out the coefficient of [tex]\( y^2 \)[/tex]:
[tex]\[ -9(y^2 - 2y) \][/tex]
To complete the square for [tex]\( y^2 - 2y \)[/tex]:
1. Take half the coefficient of [tex]\( y \)[/tex]: [tex]\( \frac{-2}{2} = -1 \)[/tex]
2. Square it: [tex]\((-1)^2 = 1 \)[/tex]
So, we rewrite [tex]\( y^2 - 2y \)[/tex] as:
[tex]\[ y^2 - 2y + 1 - 1 \][/tex]
Now we factor and adjust:
[tex]\[ -9(y^2 - 2y + 1 - 1) = -9((y - 1)^2 - 1) = -9(y - 1)^2 + 9 \][/tex]
### Step 2: Combine All Parts
Combine the completed squares:
[tex]\[ 4(x + 3)^2 - 36 - 9(y - 1)^2 + 9 - 9 = 0 \][/tex]
Simplify:
[tex]\[ 4(x + 3)^2 - 9(y - 1)^2 - 36 + 9 - 9 = 0 \][/tex]
[tex]\[ 4(x + 3)^2 - 9(y - 1)^2 - 36 = 0 \][/tex]
Move the constant to the other side and simplify:
[tex]\[ 4(x + 3)^2 - 9(y - 1)^2 = 36 \][/tex]
Divide both sides by 36:
[tex]\[ \frac{4(x + 3)^2}{36} - \frac{9(y - 1)^2}{36} = \frac{36}{36} \][/tex]
[tex]\[ \frac{(x + 3)^2}{9} - \frac{(y - 1)^2}{4} = 1 \][/tex]
Here, the equation is now in standard form.
### Step 3: Identify Key Features
Center (h, k):
In the standard form [tex]\(\frac{(x - h)^2}{a^2} - \frac{(y - k)^2}{b^2} = 1\)[/tex], we have:
[tex]\[ \frac{(x - (-3))^2}{9} - \frac{(y - 1)^2}{4} = 1 \][/tex]
So, the center is:
[tex]\[h = -3, \quad k = 1\][/tex]
Values of [tex]\(a^2\)[/tex] and [tex]\(b^2\)[/tex]:
[tex]\[a^2 = 9, \quad b^2 = 4\][/tex]
Slope of the Asymptotes:
The slopes of the asymptotes of the hyperbola given by [tex]\(\frac{(x - h)^2}{a^2} - \frac{(y - k)^2}{b^2} = 1\)[/tex] are given by [tex]\(\pm \frac{b}{a}\)[/tex]:
[tex]\[ \text{slope of asymptotes} = \pm \frac{b}{a} = \pm \frac{\sqrt{4}}{\sqrt{9}} = \pm \frac{2}{3} \][/tex]
### Summary of Key Features:
- Center:
[tex]\[h = -3\][/tex]
[tex]\[k = 1\][/tex]
- Values:
[tex]\[a^2 = 9\][/tex]
[tex]\[b^2 = 4\][/tex]
- Slope of the asymptotes:
[tex]\[ \text{slope} = \pm \frac{2}{3} \][/tex]
### Answer:
In conclusion, the key features are:
[tex]\[ h = -3, \quad k = 1, \][/tex]
[tex]\[ a^2 = 9, \quad b = \sqrt{4} = 2,\][/tex]
[tex]\[ \text{slope of asymptotes} = \pm \frac{2}{3} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.